Unveiling Antioxidant and Antiproliferative Effects of Prosopis juliflora Leaves against Human Prostate Cancer LNCaP Cells: Antioxidant and Anticancer Potential of Prosopis juliflora - Khan, Fahad; Pandey, Pratibha; Singh, Aashi; Upadhyay, Tarun Kumar; AboElnaga, Shimaa Mohammed Hasnin; Al-Najjar, Mohammad A A; Saeed, Mohd; Kahrizi, Danial (Cellular and Molecular Biology, 2022)
Herbal medications or formulations are regularly recommended by clinicians as a potential therapeutic method for a variety of human ailments, including cancer. Although Prosopis juliflora extracts have shown promise in anticancer activity, the effects on prostate cancer and the accompanying molecular mechanisms of action are still unexplored. This research aims at the antioxidant, antiproliferative, and apoptosis-inducing properties of Prosopis juliflora methanolic leaves extract in human prostate cancer LNCaP cells. The antioxidant ability of the extract was assessed using the DPPH (2, 2-diphenyl-2-picrylhydrazyl) and two additional reducing power tests. Antitumor activity was determined using MTT cell viability tests and LDH cytotoxicity assays. The probable mechanism of apoptotic cell death was further investigated utilizing a caspase-3 activation assay and qRT-PCR mRNA expression investigations of apoptotic-related genes. The results revealed that the methanol extract of Prosopis juliflora leaves contains alkaloids, flavonoids, tannins, glycosides, and phenols, all of which have substantial antioxidant activity. In vitro anticancer tests demonstrated that extract therapy resulted in a dose-dependent reduction in cell viability of LNCaP prostate cancer cells, but normal HaCaT cells showed no cytotoxic effects. Furthermore, plant extract therapy increased caspase-3 activation and mRNA expression of apoptotic-related genes, suggesting that this could be a mechanism for cancer cell growth suppression. The significance of Prosopis juliflora as a source of new antioxidant compounds against prostate cancer was emphasized in the current study. However, more study is needed to demonstrate the efficacy of Prosopis juliflora leaves extract in the treatment of prostate cancer.